Menstrual hygiene practices among adolescent girls in rural area of India - Kausheic, M. Ajay; K., Karthikeyan; A. M., Shagirunisha Rizvana; Ganesh Babu, B. (International Journal Of Community Medicine And Public Health, 2021)
Menstruation and menstrual practices still face many social, cultural, and non secular restrictions which is an enormous barrier within the path of menstrual hygiene management. In many parts of the country especially in rural areas girls aren’t prepared and aware of menstruation in order that they face many difficulties and challenges reception, schools, and work places. In rural areas, women don’t have access to sanitary products or they know little about the kinds and method of using them or are unable to afford such products due to high cost. So, they mostly believe reusable cloth pads which they wash and use again. Implementation of recent techniques like incineration can help to scale back the waste. Also, awareness should be created to stress the utilization of reusable sanitary products or the natural sanitary products made up of materials like banana fibre, bamboo fibre, sea sponges, water hyacinth, and so on.